Rosiglitazone , Metformin or both for Treatment of Polycystic Ovary Syndrome - Mohammed A.Taher; Waleed R. Sulaiman; Hillal Y. Al-Khairi (College of Pharmacy University of Baghdad, 2017)
This study was designed to show the advantages of using the combination of metformin and rosiglitazone over using each drug alone in treatment of women with polycystic ovary syndrome (PCOS).Forty four women with PCOS were classified into 3 groups , group 1 received rosiglitazone (4mg/day) for 3 months , group Î™Î™ received metformin ( 1500 mg/day)for three months and groupÎ™Î™Î™ received the combination ( rosiglitazone 4mg/day + metformin 1500 mg/day) for the same period of treatment   . The blood samples were drawn before treatment and after 3 months of treatment . The fasting serum glucose , insulin , progesterone , testosterone , leutinizing hormone were measured before and after treatment. The reduction of serum insulin , glucose ,homostasis model assessment of insuline resistance ( HOMA-IR) , LH and testosterone levels were greater in the group received the combination of rosiglitazone with metformin than that those taken each one alone. Testosterone levels decreased significantly (P<0.05) from baseline level 1Â±0.04ng/ml to 0.073Â±0.32ng/ml  after treatment with combination.The rate of ovulation is 29.4%,36.4% , 62.5% in rosiglitazone , metformin and combination of both, respectively.The combination of rosiglitazone with metformin has more beneficial effect on ovulation rate.  Key words: polycystic ovary syndrome, rosiglitazone, metformin, ovulation rate  .